(untitled) (Web of Teachers: Inderscience Research, 2026)
The formation of self-management skills in students has become one of the central problems of contemporary education because academic success increasingly depends not only on subject knowledge but also on the learner’s ability to regulate time, effort, emotions, attention, goals, and behavioral choices. In higher and general education alike, self-management acts as an integrative competence that connects self-awareness, motivation, planning, monitoring, reflection, and responsibility for outcomes. The present article examines the formation of self-management skills in students from a pedagogical and psychological perspective.